2018
DOI: 10.1590/1809-4430-eng.agric.v38n3p417-425/2018
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Substrate and Species Arrangement of Cultivated Grasses on the Efficiency of Horizontal Subsurface Flow Constructed Wetlands

Abstract: We aimed to evaluate the efficiency of six different horizontal subsurface flow constructed wetlands (HSSF-CWs), with different substrates (gravel and crushed PET bottles), which also varied in relation to the presence and arrangement of plant species (elephant grass and Tifton 85 bermudagrass) in the removal of pollutants from a bulk milk cooling tank (MTWW). Each bed was fed at a flow rate of 0.18 m 3 d -1 and average organic load rate (OLR) of 318 kg ha -1 d -1 of BOD5, with hydraulic detention time (HRT) o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 25 publications
(28 reference statements)
0
12
0
Order By: Relevance
“…In order to investigate possible efficiency loss of pollutants' removal from the system, the operation was divided into periods: Period I (data generated from April to December 2015 in the experiment conducted by Saraiva et al (2018)) and Period II (monitoring of the system from March 11, 2016 until December 15, 2016), with the application of WWMT. Each of these phases was performed by a different researcher, with different research objectives.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…In order to investigate possible efficiency loss of pollutants' removal from the system, the operation was divided into periods: Period I (data generated from April to December 2015 in the experiment conducted by Saraiva et al (2018)) and Period II (monitoring of the system from March 11, 2016 until December 15, 2016), with the application of WWMT. Each of these phases was performed by a different researcher, with different research objectives.…”
Section: Methodsmentioning
confidence: 99%
“…To compare the removal efficiencies between Period I and Period II, the "t" test was used for independent data at 5% significance. Table 1 shows the mean values of the surface application rates during experimental monitoring of the systems, Period I (April to December 2015) (Saraiva et al, 2018) and Period II, the period of this study (April to December 2016). As observed, only the surface loading rate of TP differed significantly according to the t-test.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Button et al (2016) observed an influence of the cultivation of Engenharia Agrícola, Jaboticabal, v.39, n.5, p.668-675, sep./oct. 2019 intercropping species (two by two) on the microbial community in CWs, and thus there could be an effect on the unit performance, which was demonstrated by Saraiva et al (2018). Consequently, there may be a higher extraction capacity for species cultivated under this condition.…”
Section: Introductionmentioning
confidence: 96%